A stochastic forward-looking model to assess the profitability and solvency of European insurers - Elia Berdin; Christoffer Kok; Cosimo Pancaro (European Central Bank (ECB), 2017)
In this paper, we develop an analytical framework for conducting forward-looking assessments of profitability and solvency of the main euro area insurance sectors. We model the balance sheet of an insurance company encompassing both life and non-life business and we calibrate it using country level data to make it representative of the major euro area insurance markets. Then, we project this representative balance sheet forward under stochastic capital markets, stochastic mortality developments and stochastic claims. The model highlights the potential threats to insurers solvency and profitability stemming from a sustained period of low interest rates particularly in those markets which are largely exposed to reinvestment risks due to the relatively high guarantees and generous profit participation schemes. The model also proves how the resilience of insurers to adverse financial developments heavily depends on the diversification of their business mix. Finally, the model identifies potential negative spillovers between life and nonlife business through the redistribution of capital within groups.
Keywords: G20; G22; G23; 330; Financial Stability; Insurance; Interest Rate Risk; Stress Test